Improvement of fine motor development in preschool age children by using coloring playing techniques - Putri, Ghosa Oktaviani; Juliningrum, Peni Perdani; Merina, Nuning Dwi (Universitas Muhammadiyah Semarang, 2023)
The next stage of growth will be determined by children's optimal development from an early age. The preschool years are critical for the development of a wide range of abilities. Preschoolers are generally youngsters that develop swiftly and have a wide range of talents. This potential will be realized so that youngsters can reach their full potential. This potential will be realized so that youngsters can reach their full potential. As a result, proper conditions or instruction are required for a child's growth. Various developmental difficulties in children, such as motor delays, language, behavior, autism, and hyperactivity, have been on the rise in recent years. As a result, for children's growth and development, adequate conditions or education are required. The goal of this study was to see how colouring affects children's fine motor development when they are in preschool. The total number of students in this study was 32. In this study, the researchers employed a Quasi Experiment with a nonequivalent control group design. The entire sampling strategy was employed in this investigation. There were as many as 32 responders in the sample. The Wilcoxon test yielded p-values of 0.001 and 0.083 in the data analysis. The findings of data analysis utilizing the Mann-Whitney test, namely a p-value of 0.000 < (0.05), indicate that Ho is not significant. This shows that colouring stimulation influences the fine motor development of preschool children in this study.